2019
DOI: 10.1155/2019/5962065
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Poor Eye Drop Administration Technique and the Role of Patient Education among Hong Kong Elderly Population

Abstract: Objectives. To identify the risk factors for poor eye drop application technique in treatment-naïve subjects and to assess if patient education can benefit these subjects. Methods. Chinese subjects above 60 years were recruited. Questionnaires, including Barthel index; Lawton’s instrumental activities of daily living (ADL); Fatigue, Resistance, Ambulation, Illnesses, and Loss of Weight (FRAIL) scale; and Montreal Cognitive Assessment (MoCA), were used to correlate with eye drop application technique (before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…During the use of eye drops, 78/244 (32%) patients had a contact history with the eyelids, eyelashes, or conjunctiva, which was consistent with the results reported in other literature (20,21). Previous studies showed that the poor infusion capability of glaucoma patients was related to age, limited education, and poor hands-on flexibility (22,23). In the current study, the contamination rate was not associated with the age and education level of glaucoma patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During the use of eye drops, 78/244 (32%) patients had a contact history with the eyelids, eyelashes, or conjunctiva, which was consistent with the results reported in other literature (20,21). Previous studies showed that the poor infusion capability of glaucoma patients was related to age, limited education, and poor hands-on flexibility (22,23). In the current study, the contamination rate was not associated with the age and education level of glaucoma patients.…”
Section: Discussionsupporting
confidence: 90%
“…However, unfortunately, the experience of such surgery did not improve the health awareness of patients, and there was no statistical difference in the contamination rate of drippers between the operation group and the non-operation group. Choy et al (23) reported that the infusion success rate can be significantly improved after eye drop skills training in a group of elderly patients. Thus, some specially-designed eye drop bottles (24,25) or special eye drop aid systems (26) may play a vital role in addition to improving the infusion skills of eye drops and improving the safety awareness of hand hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Improper drop instillation has been cited as an important feature in non-adherence to glaucoma medications. [11][12][13][14][15][16][17] Although we did not directly observe patients instilling their medication, as only 42% stated they had received instruction on how to do so and 26% of patients reported an insufficient time interval (< five minutes) between consecutive medications, then it is reasonable to assume some patients would be doing this incorrectly.…”
Section: Discussionmentioning
confidence: 96%
“…1 Previous studies have demonstrated that patient adherence to topical medication in conditions, such as glaucoma can be poor and appears influenced by a number of factors, such as understanding of disease, [2][3][4] rationale of treatment, 2,5,6 having a simplified treatment regimen, [7][8][9][10] ease of drop instillation and whether they are dispensed in single use containers or multiple-use bottles. [11][12][13][14][15][16][17] In the ophthalmic literature there is very little information on adherence in inflammatory eye disease. 18 We wished to evaluate adherence to topical medication in patients with inflammatory eye disease in a tertiary Eye Centre setting and to identify factors that may influence this.…”
Section: Introductionmentioning
confidence: 99%
“…Using topical eye drops is generally considered to be the most convenient and safe approach for treating ocular conditions, including glaucoma, and generally leads to the highest patient acceptability. However, as many as nine out of ten patients are unable to properly instil eye drops 147 , 148 , leading to an increased risk of under-medication or over-medication and, potentially, resulting in poor outcomes and unnecessarily high treatment costs. Long-acting DDSs, including clinically available injectable depots, refillable devices and in situ-forming hydrogels, are promising strategies to improve medication adherence, mainly because they minimize the need for frequent drug administration.…”
Section: Trends In Adherence By Disease Typementioning
confidence: 99%